Use of Cooperative Learning Methods STAD Strategies to Improve students' Abilities in Qira'ah (Experimental Research in Ma'had al-Uluum ad-Diniiyati al-Islaamiyyati Samalanga) - Murdani murdani; Mahdir Muhammad; Bani Amin; Mira Ulfa; Muhammad Haikal (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
Qira’ah is one of the four language skills, even it is the biggest intermediaries to get knowledge, either shari'a or general. Teachers in salafiah colleges using classical methods in the teaching of Qira’ah in which teachers are more involved and the lack of attention, activity and creativity of students, so the ability to read correctly the students Less increase. And because the teachers need to be more suitable methods, one of which is a cooperative learning STAD. This research was conducted in ma'had al-uluum ad-diniiyati al-islaamiyyati Samalanga. The population is all students in second class ma'had al-uluum ad-diniiyati al-islaamiyyati Samalanga and the sample was second H class totaling 34 students and second I class was 34 students. The purpose of this research was to know the effectiveness of using in Ma’had al-uluum ad-diniiyati al-islaamiyyati Samalanga. This research is an experimental research. The results showed that the application of cooperative learning STAD qiraah was effective in improving the ability of students, it can be seen from the t-hitung is bigger than t-table, that is 2.83> 1.99.